Berichtigungsliste der Griechischen Papyrusurkunden aus Ägypten : Konkordanz zu Band VIII-XI (B.L. Konkordanz II) - Bakker, M. J. (Berichtigungsliste der Griechischen Papyrusurkunden aus Ägypten., 2007)
The Berichtigungsliste der Griechischen Papyrusurkunden aus Ägypten is a tool of outstanding importance for anyone publishing or studying Greek papyrus documents. The new Konkordanz zu Berichtigungsliste Band VIII-XI or in short B.L. Konkordanz II facilitates finding corrections to published papyri. After the model set out by B.L. Konkordanz I ( Konkordanz und Supplement zu Berichtigungsliste Band I-VII , Leuven 1989), it guides the user first to the main edition of each text, and refers there to the corrections and other remarks in B.L. VIII-XI that must still be taken into account. References to outdated corrections of older editions have been omitted, so that the user of the Berichtigungslisten does not look up references to no purpose. Among the information provided, special attention is drawn to corrected dates, published photographs and important new editions of texts. Anticipating the publication of B.L. XII in the near future, new editions in Sammelbuch XXIV and XXVI have already been incorporated. B.L. Konkordanz II, an indispensible tool for users of the printed editions of the Berichtigungsliste.